Assessing the challenges faced by black built environment professionals as business owners - Nkoana, Koketso (My University, 2022)
There is a growing concern about the limited representation of black Built Environment Professionals (BEP) as business owners in the industry. This study then attempts to address the imbalance in the industry by highlighting the challenges faced by black BEPs. The greatest challenge that was pointed out by the investigation is the perceptions of economic transformation in the industry. The study further highlights the following challenges, economic structure, racial profiling, monopolisation of industry funding, red tape, corruption, experience, access to market, regulation, subcontracting and policy and industry planning. Thus, there is a limited representation of black BEPs as business owners. The researcher has observed some positive outputs from the transformative programmes implemented in the industry. As some efforts toward transformation have yielded positive results and managed to create opportunities in the industry for black BEPs. However, the study outlines the lingering concern of the disconnect that exists between the professional experience of these BEPs and the capacity of their businesses. there is also a concern around the efforts of the industry to develop Black BEPs as business owners as opposed to them simply being technical contributors and thus seen as employees. The study outlines the need for BEPs to be seen as businesses as they primarily trade in intellectual property.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Public Development and Management (50%) to the Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2022
Keywords: Black Built Environment Professionals (BEP); Business owners; UCTD; SDG-8: Decent work and economic growth